'Localism and intimacy, and… other rather imponderable reasons of that sort': A qualitative study of patient experience of community hospitals in England. (3rd November 2022) - Davidson, Deborah; Williams, Iestyn; Glasby, Jon; Paine, Angela Ellis
Abstract: Debates over the value and contribution of community hospitals are hampered by a lack of empirical assessment of the experience of patients using these services. This paper presents findings from a study which included a focus on patient and family‐carer experiences of community hospitals in England. We adopted a qualitative design involving nine case study hospitals. Data collection included interviews with patients ( n = 60), carers ( n = 28) and staff ( n = 89). Through patients and carers highlighting the value of community hospitals feeling 'close to home', providing holistic and personalised care and supporting them through difficult transitions, the study confirms the importance of functional and interpersonal aspects of care, while also highlighting the importance of social and psychological aspects. These included having family, friends and the community close, maintaining social connections during periods of hospital treatment, and feeling less anonymous and anxious when attending the hospital due to the high levels of familiarity and connectedness. Although the experiences uncovered in this study were not uniformly positive, patients and carers placed a high overall value on the care provided by community hospitals, often arguing that these were distinctive when compared to their experiences of using other health and care services. The study suggests the need to weigh the full range of these dimensions of patient experience—functional, interpersonal, social and psychological—when assessing the role and contribution of community hospitals.